The Role of Academic Supervision in Controlling the Curriculum - Harly, Muhammad Riadhi; Lubis, Nasib Samsuri; Syaifuddin, H. Muhammad; Afandi, Muslim (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Academic supervision plays a crucial role in controlling and ensuring the quality of the curriculum in educational institutions. The main purpose of academic supervision is to monitor, evaluate, and improve the implementation of the curriculum so that it can meet the educational standards that have been set. This supervision process involves various activities such as classroom observation, teacher performance assessment, analysis of student learning outcomes, and constructive feedback to teaching staff. Through effective supervision, educational institutions can identify strengths and weaknesses in curriculum implementation, as well as develop relevant improvement strategies. In addition, academic supervision also serves as a quality control mechanism that ensures that the curriculum remains relevant to the development of science and the needs of society. The results of the study show that structured and continuous academic supervision can improve the quality of teaching, motivate.